Extraordinary synergetic effect of precursors in laser CVD deposition of SiBCN films. Issue 16 (December 2019) - Merenkov, I.S.; Katsui, H.; Khomyakov, M.N.; Sulyaeva, V.S.; Pushkarev, R.V.; Tu, R.; Goto, T.; Kosinova, M.L.
Abstract: Herein, we report on the synergetic effect of simultaneously using of hexamethyldisilane (HMDS) and trimethylamine borane (TMAB) as precursors for a high-rate laser chemical vapor deposition of SiBCN films. The major components of obtained films were successfully controlled by deposition temperature from B4 C to graphene and β-SiC. In addition, B4 C and graphene/β-SiC films were synthesized from TMAB and HMDS, respectively. The growth rate of SiBCN films was extremely high (up to 1620 μm/h) in contrast to 18 μm/h and 415 μm/h for graphene/β-SiC and B4 C films, respectively. Thermodynamic modeling demonstrated that reactions between nitrogen- and silicon-containing gas species during double-source CVD process could be the possible reason of synergism and growth rate increasing. A mechanical study demonstrated very high hardness (up to 43 ± 7 GPa) and wear resistivity of the SiBCN films. The reported results reveal a significant potential of precursor synergism for the design of new materials with enhanced properties.